Different Antiplatelet Strategies in Patients With New Ischemic Stroke While Taking Aspirin. Issue 1 (January 2016) - Kim, Joon-Tae; Park, Man-Seok; Choi, Kang-Ho; Cho, Ki-Hyun; Kim, Beom Joon; Han, Moon-Ku; Park, Tai Hwan; Park, Sang-Soon; Lee, Kyung Bok; Lee, Byung-Chul; Yu, Kyung-Ho; Oh, Mi Sun; et al.
Abstract : Background and Purpose—: Selecting among different antiplatelet strategies when patients experience a new ischemic stroke while taking aspirin is a common clinical challenge, currently addressed by a paucity of data. Methods—: This study is an analysis of a prospective multicenter stroke registry database from 14 hospitals in South Korea. Patients with acute noncardioembolic stroke, who were taking aspirin for prevention of ischemic events at the time of onset of stroke, were enrolled. Study subjects were divided into 3 groups according to the subsequent antiplatelet therapy strategy pursued; maintaining aspirin monotherapy (MA group), switching aspirin to nonaspirin antiplatelet agents (SA group), and adding another antiplatelet agent to aspirin (AA group). The primary study end point was the composite of stroke (ischemic and hemorrhagic), myocardial infarction, and vascular death up to 1 year after stroke onset. Results—: A total of 1172 patients were analyzed for this study. Antiplatelet strategies pursued in study patients were MA group in 212 (18.1%), SA group in 246 (21.0%), and AA group in 714 (60.9%). The Cox proportional hazards regression analysis showed that, compared with the MA group, there was a reduction in the composite vascular event primary end point in the SA group (hazard ratio, 0.50; 95% confidence interval, 0.27–0.92; P =0.03) and in the AA group (hazard ratio, 0.40; 95% confidence interval, 0.24–0.66; P <0.001). Conclusions—: This study showed that, compared with maintaining aspirin, switching to or adding alternative antiplatelet agents may be better in preventing subsequent vascular events in patients who experienced a new ischemic stroke while taking aspirin. Abstract : Supplemental Digital Content is available in the text.